1999
DOI: 10.1161/01.hyp.34.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, Coronary Arterial Remodeling, and Myocardial Infarction After Nitric Oxide Inhibition in SHR

Abstract: Abstract-This study was designed to investigate the relationship between apoptosis (programmed cell death) and coronary arterial remodeling in spontaneously hypertensive rats (SHR) following prolonged nitric oxide synthesis inhibition. In addition, we evaluated whether the development of coronary arterial smooth muscular cell apoptosis was related to hemodynamics or to vascular hypertrophy. Three groups of 20-week-old male SHR were investigated: controls, and two groups that received two doses of N G -nitro-L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 66 publications
2
32
0
Order By: Relevance
“…NO is an important modulator of blood pressure due to its vasodilatory capability (36,37) and plays a critical role in VEGF-induced angiogenesis and vascular hyperpermeability (38). In addition, several studies have demonstrated that NO is involved in modulation of cell proliferation, differentiation, and apoptosis in the vasculature (39). Furthermore, there is increasing evidence that NO-derived oxidants, such as peroxynitrite, might be important in situ mediators of oxidative injury in experimental models of retinal ischemia (40).…”
Section: Figurementioning
confidence: 99%
“…NO is an important modulator of blood pressure due to its vasodilatory capability (36,37) and plays a critical role in VEGF-induced angiogenesis and vascular hyperpermeability (38). In addition, several studies have demonstrated that NO is involved in modulation of cell proliferation, differentiation, and apoptosis in the vasculature (39). Furthermore, there is increasing evidence that NO-derived oxidants, such as peroxynitrite, might be important in situ mediators of oxidative injury in experimental models of retinal ischemia (40).…”
Section: Figurementioning
confidence: 99%
“…Therefore, the efficacy of antihypertensive drugs on inhibition of hypertensive tissue injury and preservation of cardiovascular organ function is a matter of primary importance. Several studies have investigated the protective effects of antihypertensive drugs against cardiovascular organ injury using various animal models of hypertension, including mineralocorticoid-salt administration, 1,2) renovascular hypertension, [3][4][5] renal ablation 6,7) and nitric oxide synthase inhibition, 8,9) in which hypertensive organ injury progresses rapidly over a period of several weeks to months. However, this rapid temporal course of organ damage does not accurately reflect the organ damage that occurs over a span of decades in humans with essential hypertension.…”
mentioning
confidence: 99%
“…However, a differential regulation of MMP release and activation in vivo versus in vitro may account for this discrepancy. The inhibition of NO production as well as the degradation of the ECM facilitate apoptosis (36,48,63). Oxidative stress instigates the decrease in endothelial NO availability (10,65) as well as increases the levels of cytokines, growth factors, and neurohormones (11,17,26).…”
mentioning
confidence: 99%